An idealized stratospheric model useful for understanding differences between long‐lived trace gas measurements and global chemistry‐climate model output. Issue 10 (19th May 2016) - Ray, Eric A.; Moore, Fred L.; Rosenlof, Karen H.; Plummer, David A.; Kolonjari, Felicia; Walker, Kaley A.
Abstract: We use a modified version of the tropical leaky pipe (TLP) model of the stratosphere to explore how well an idealized model can (1) reproduce global chemistry‐climate model (CCM) output and (2) constrain transport characteristics necessary to replicate measurements of long‐lived trace gases. The version of the TLP model we use includes the simulation of long‐lived trace gases, such as SF6 and CO2, as well as photochemically active trace gases such as CFC‐11, CFC‐12, and N2 O. The TLP model was found to accurately replicate trace gas output from the Canadian Middle Atmosphere Model (CMAM) for time‐averaged profiles in the tropics and each extratropical region. Given confidence that the TLP model represents the basic transport features in CMAM we then used the TLP model to interpret differences between CMAM output and measurements from the Atmospheric Chemistry Experiment and balloons. The TLP model is shown to uniquely determine residual mean circulation and recirculation (mixing between the extratropics and tropics) changes necessary for CMAM to more accurately simulate the measurements. Such guidance on these transport parameters is novel due to the relatively high precision and the simultaneous derivation of important parameters, as compared to previous studies. The TLP model can ideally be used as a bridge between measurements and CCMs to potentially allow more targeted modification of the CCMs than would otherwise be possible. Key Points: Idealized stratospheric model accurately simulates CMAM trace gas and mean age profiles Idealized model provides quantitative transport guidance for CCM to better simulate observations Specific suite of trace gas measurements provides unique transport information to validate CCMs